Identification of simple sequence repeat (SSR) markers linked to interspecific potato somatic hybrids - TIWARI, JAGESH K; ZINTA, RASNA; LUTHRA, S K; DALAMU, DALAMU; RAWAT, SHASHI; BUCKSETH, TANUJA; SINGH, RAJESH K; BHARDWAJ, VINAY; KUMAR, MANOJ (The Indian Journal of Agricultural Sciences, 2022)
The aim of present study was to identify simple sequence repeat (SSR) markers linked to potato somatic hybrid progenies. A total of 50 breeding lines (parents and progenies) were analyzed using 59 simple sequence repeat (SSR) markers. Of which, SSR marker STM0003 clearly distinguished the parents i.e. somatic hybrid P8 (Solanum tuberosum dihaploid C-13 + wild species S. pinnatisectum) and potato cv. Kufri Jyoti, and their progenies (MSH-14/112, MSH-14/113, MSH-14/114, MSH-14/115, MSH-14/116, MSH-14/122 and MSH-14/123). STM0003 showed three distinct alleles (103, 132 and 144 bp), where both P8 and progenies contained 103 and 144 bp, and Kufri Jyoti had 132 and 144 bp alleles. On the other hand, STI0001 distinguished progenies namely MSH/17-16 (Kufri Garima × Crd10), MSH/17-25 (Kufri Garima × P10) and MSH/17- 27 (Kufri Jyoti × Crd 16) with respect to their parents, and STI0001 contained six alleles (169, 172, 175, 178, 184 and 188 bp). The study suggests that STM0003 and STI0001 are diagnostic markers to identify these somatic hybrid derived progenies and parents.